Fifty weapons that changed the course of history - Levy, Joel 1971- (Firefly Books, 2014)
Looks at fifty weapons that have helped shape the last 3,500 years, from the very first hand-ax to the AK-47 and beyond
Includes bibliographical references (pages 218-220) and index
Keywords: Geschichte; History; Weapons; Weapons -- History; Military weapons -- History; Waffe